(untitled) (Research, Society and Development, 2021)
Early menopause is a condition that affects 1% of women, consisting in the permanent cessation of menstruation due to the loss of ovarian function before the age of 40 years. This article does a quantitatively analysis of the bibliography that cites the term in four different indicators: a) is there a disparity between men and women in research on the subject? b) In what regions are the institutions of the authors of the selected papers? c) What are the areas of knowledge of the authors who cite early menopause? d) Is early menopause treated as the focus of the paper or not? A qualitative analysis is then made by categorizing the main themes of the article’s relation to the early menopause: those that relate early menopause to osteoporosis; those that relate it to cancer; those that relate it to menopause generically; articles that cite it but do not have enough internal cohesion or volume for an exclusive category. It is concluded that more women are authors in articles that cited the term; that the Southeast and Northeast concentrate the majority of authors, with the presence of researchers from the northern region being lower than the others; that despite the fact that many areas of knowledge are present, medicine is the one with the heaviest weight; that early menopause is not treated as the main focus in any of the articles found. These questions show that there is room for the expansion of studies on early menopause in Brazil, both when studying it as a biological phenomenon or public health policies and research on it.